241 STOPPCASCADE: DEVELOPMENT OF A NOVEL EXPLICIT SCREENING TOOL FOR POTENTIALLY CLINICALLY RELEVANT PRESCRIBING CASCADES IN OLDER ADULTS. (25th October 2022) - Randles, M; Gallagher, P; O'Mahony, D
Abstract: Background: Prescribing cascades represent an important, often underrecognized, element of problematic polypharmacy. Cascades occur when an Adverse Drug Event (ADE) is misinterpreted as a new medical condition, with the subsequent prescription of another, potentially inappropriate drug. Our objective was to develop and validate an explicit list of potentially clinically relevant prescribing cascades in older adults to facilitate the detection of more common and clinically important prescribing cascades and assist clinicians in medication review. Methods: A structured literature search of PubMed, Cinahl and Google Scholar was undertaken. Search terms included Prescribing Cascades OR Cascades OR Cascade AND Older Adults OR Adults Over 65 OR Older People OR Gero* OR Geri*. We included adults aged ≥65 including studies in all settings i.e. community, hospital and residential care. We included all study designs including reviews, experimental and observational studies, case series and case reports. We also included published abstracts from scientific meetings in the literature search. Studies that didn't include prescribing cascades in the abstract, studies with no access to full text article or English version of article and studies exclusively describing patients aged ≤65 were excluded. A physiological systems-based short-list was compiled with Anatomical Therapeutic Chemical codes identifying the initial prescribed drug (Drug A). Three assessment panellists (academic geriatricians) were asked to evaluate each individual published cascade and the accompanying evidence using a 5-point Likert scale to evaluate each cascade for inclusion/exclusion in the list. Potential cascades scored Likert 4 or 5 by 2 or 3 of the panellists were included in the final list. Results: 131 potential cascades were reviewed by the panel, 71 individual cascades were accepted, involving 41 drugs/drug classes. Conclusion: The STOPPCascade list comprises 71 potentially important prescribing cascades in older adults. This novel explicit list is designed to identify potential prescribing cascades and to facilitate appropriate deprescribing.